Antitumor Effects and Protective Effects Against DOxorubicin-induced Testicular Toxicity of Cultivated Wild Ginseng Extract in the B16/F10 Melanoma-Bearing C57BL/6 Mice - Min,Byung-Il; Kim,Ho-Hyun; Seo,Il-Bok; Kwon,Ki-Rok (Korean Pharmacopuncture Institute, 2007)
Objectives : This research was executed to verify antitumor effect and protective effect on doxorubicin(Doxo)-induced toxicity of Cultivated Wild Ginseng(CWG) and synergic effect of CWG with Doxo in B16/F10 melanomas-bearing C57BL/6 mice. Methods : To evaluate protective effect on doxorubicin(Doxo)-induced toxicity and enhancing effect on the antitumor activity of Doxo, CWG water extract(0.5 ml) was intraperitoneally injected for 10 days, in combination with intraperitoneal injection of Doxo(4 mg/kg) on days 12, 16, 19, to mice subcutaneously inoculated with B16/F10 melanoma cells. In order to investigate antitumor effect of CWG, CWG water extract(0.5 ml) was intraperitoneally injected for 10 days to mice subcutaneously inoculated with B16/F10 melanoma cells. Results : The body weights of melanoma-bearing mice increased following B16/F10 cells inoculation. In contrast, such an increase in body weights was significantly attenuated by Doxo administration. Whereas CWG inhibits the decrease in body weights induced by Doxo. The tumor volume and tumor weights of melanomas-bearing mice dramatically increased following B16/F10 cells inoculation, In contrast, such an increase in tumor volume and tumor weights were significantly attenuated by Doxo or CWG administration. But the synergic effect of CWG with Doxo was not observed. The reduction of cellularity of seminiferous epithelia, level of spermatogonium and spermatid induced by Doxo was recovered by CWG administration. BrdU labeling index of spermatogonium was remarkably decreased in Doxo group but was no change in CWG group. Whereas the incidence and intensity of BrdU labelled spermatocytes and spermatids were increased by CWG administration than those of Doxo group. Conclusions : The obtained results suggest that CWG have antitumor effect and protective effect on doxo-induced testicular toxicity. This effect might be mediated through the supplementation of vital energy.